2021
DOI: 10.1038/s41598-020-79522-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between distribution and severity of non-perfusion and cytokine levels and macular thickness in branch retinal vein occlusion

Abstract: We aimed to investigate the relationship between non-perfusion on ultra-widefield angiography (UWF FA) and aqueous cytokine levels and central macular thickness (CMT) in eyes with branch retinal vein occlusion (BRVO). Thirty-five eyes with treatment-naïve BRVO were included. Non-perfusion area (NPA) for partial and complete ischemia was manually segmented and the ischemic index (ISI) for each was calculated using stereographically projected UWF FA for four different retinal zones. Partial and complete ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Based on the data obtained ( P > 0.05), no significant association was identified between BCVA and the degree of ME in patients. However, Ryu et al [ 26 ] demonstrated a strong correlation between baseline BCVA and CMT, in contrast to our findings. The finding of our study indicates that the degree of BCVA and ME are not significantly associated, which is similar to the findings of Fujino et al [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Based on the data obtained ( P > 0.05), no significant association was identified between BCVA and the degree of ME in patients. However, Ryu et al [ 26 ] demonstrated a strong correlation between baseline BCVA and CMT, in contrast to our findings. The finding of our study indicates that the degree of BCVA and ME are not significantly associated, which is similar to the findings of Fujino et al [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This could be because the level of cytokines expressed in aqueous humor does not correctly reflect the real state of the retina, as the level of cytokines expressed in the aqueous humor is modified by their diffusion rate and interaction with the extracellular matrix. The damage of cytokines and their cascades to photoreceptors and neurons in the inner layer of the retina cannot be synchronized [ 26 ]. Therefore, there is no apparent correlation between BCVA and the expression levels of VEGF, IL-6, ICAM-1, and VCAM-1 in the aqueous humor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the retina, IL-6 is related to ischemia and vessel injury. In BRVO, IL-6 is significantly related to NPA ( 166 ) and caused macular edema secondary to BRVO ( 146 ). During inflammation, IL-6 binds with IL-6R forming a compound which then combines with gp130 and activates the downstream STAT3 and JAK-MAPK pathways.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“… 16 Moreover, the regions of peripheral CNP detected on UWFFA were further subclassified as partial CNP, complete CNP, and total CNP. 17 Partial CNP was characterized by the presence of a cluster of small fragmented areas of hypofluorescence, with dilation and irregular patterns in the capillary network; complete CNP was defined as a contiguous area of hypofluorescence due to retinal capillary loss and the obstruction of the precapillary arterioles and postcapillary venules, with the remaining precapillary arterioles and postcapillary venules being dilated and tortuous. 17 Total CNP was the sum of the 2 previous categories.…”
Section: Methodsmentioning
confidence: 99%